"Bypass the Lying Mouths": How Does the CCP Tackle Information Distortion at Local Levels?. (5th December 2016) - Gao, Jie
Abstract: The deliberate distortion of the work accomplishments of local governments is a growing concern for China's leaders in the reform era. How do they tackle this problem and gather reliable data? This study argues that the CCP has developed bypassing strategies to remedy the deficiencies of the statistical system which is vulnerable to artificial data distortion. By employing these strategies, authorities requiring authentic information can directly access the raw data, thereby bypassing lower-level officials who have incentives to distort performance information in the level-by-level reporting process. This study shows that the adoption of bypassing strategies enhances the capacity of the party-state to gather local intelligence. Although the strategies are limited in their ability to ensure the quality of certain types of data, their use should improve the quality of key information on the performance of local governments in the long term. 摘要: 地方政府工作实绩的信息造假问题已成为影响改革发展的顽疾。中国领导人是如何应付这个问题并收集真实信息的呢? 本研究发现, 中国共产党已发展出一种规避型的信息收集策略以弥补统计系统的短板。通过这种策略, 需要真实信息的一方可以直接接触到原始数据, 从而避开了下级官员在传统的层层汇报的过程中可能对绩效信息进行造假的行为。本研究认为, 规避型策略的使用加强了党和国家在地方收集信息情报的能力。尽管在收集某些数据方面仍有其局限性, 但从长远来看, 这一策略将提高与地方政府绩效相关的核心信息的质量。